2017
DOI: 10.1021/acs.chemmater.7b00255
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Surgical Adhesive and Hemostatic Materials: Synthesis, Properties, and Application of Thermoresponsive Polypeptides

Abstract: In this study, thermoresponsive and mussel-inspired polypeptides were synthesized using ring-opening polymerization of α-amino acid derivatives of N-carboxyanhydride (NCA). The tissue adhesive properties of these polypeptides were evaluated using in vitro adhesive strength tests on porcine skin and bone. The results indicated that the species of the functional polypeptide side groups and the adhesive temperature have a significant influence on the adhesion strength. The maximum of the lap-shear adhesion streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 81 publications
(131 reference statements)
0
41
0
Order By: Relevance
“…Thus, the mass of formazan is proportional to the number of living cells. 49 The absorbance of the dimethyl sulfoxide solution with formazan is determined by microplate microscopy. The cytotoxicity of QCT–TTO–pADM is determined by an MTT assay.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the mass of formazan is proportional to the number of living cells. 49 The absorbance of the dimethyl sulfoxide solution with formazan is determined by microplate microscopy. The cytotoxicity of QCT–TTO–pADM is determined by an MTT assay.…”
Section: Resultsmentioning
confidence: 99%
“…When heated above LCST, p(NIPAAm) becomes hydrophobic allowing catechol to be exposed for adhesion. Bioadhesive based on thermoresponsive peptide consisting of polyglutamic acid functionalized with oligomeric diethylene glycol monomethyl ether (poly(EG 2 ‐Glu)) exhibited enhanced adhesion at body temperature as compared to results obtained at room temperature . This increase in measure adhesive property is due to an increased in the cohesive property of poly(EG 2 ‐Glu) at body temperature.…”
Section: Multifunctional Biomedical Adhesivesmentioning
confidence: 98%
“…The intact cell monolayer can be successfully obtained on the thermoresponsive cell culture dish [83]. Lu et al synthesized a series of thermoresponsive polypeptides incorporated with various functional side groups [84]. They found that the polypeptides showed excellent biodegradability, biocompatibility, and mechanical properties in in vitro adhesion tests with no cytotoxicity.…”
Section: Applicationsmentioning
confidence: 99%